Diagnosis and management of iatrogenic ureteral injury in total laparoscopic hysterectomy - Akpak, Yaşam Kemal; Kantarcı, Sercan; Oral, Serkan; Duran, Tuğkan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Ureteral injury is common in gynecological surgeries due to the proximity to organs. The risk of ureteral injury is higher in laparoscopic hysterectomy operations compared to abdominal or vaginal hysterectomies. Obesity, endometriosis, pelvic adhesions, history of previous surgery, enlarged uterus, and intraoperative hemorrhage are some of the risk factors identified for ureteral injury. Intraoperative cystoscopy and postoperative urinary ultrasonography can be used in the diagnosis of early ureteral injury. Management of ureteral injury differs according to the extent, type, and localization of the injury. In evaluating the ureteral injury, early diagnosis and early repair in appropriate patients are essential in morbidity and medicolegal.